2020
DOI: 10.1111/opo.12657
|View full text |Cite
|
Sign up to set email alerts
|

The association between digital screen time and myopia: A systematic review

Abstract: Purpose Digital screen time has been cited as a potential modifiable environmental risk factor that can increase myopia risk. However, associations between screen time and myopia have not been consistently reported. Although myopia prevalence increased before the massive use of digital devices in some countries, with the rise being influenced by education, there may be an added recent effect of screen time. The aim of this systematic review is to determine the association between screen time and the risk of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
163
3
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(178 citation statements)
references
References 50 publications
4
163
3
8
Order By: Relevance
“…Other researchers have related a higher risk of developing myopia with shorter distances for reading (<20 cm) and longer and continuous periods (>45 min), instead of joining to the total time in near activities (17). In this sense, a recent study has concluded that results are mixed and that more studies are needed to evaluate the association between screen time and myopia (36).…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have related a higher risk of developing myopia with shorter distances for reading (<20 cm) and longer and continuous periods (>45 min), instead of joining to the total time in near activities (17). In this sense, a recent study has concluded that results are mixed and that more studies are needed to evaluate the association between screen time and myopia (36).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown adverse ophthalmological impacts associated with screen time. A meta-analytic review of 15 studies found a pooled odds ratio (OR) of myopia was 1.02 (95% confidence interval [CI]: 0.96 -1.08) in a sample of 49789 children (Lanca & Saw, 2020). A major proportion of evidence-based reviews report higher risks of noncommunicable diseases associated with screen time.…”
Section: Covid-19 and Rising Trends Of Screen Time: Public Health Conmentioning
confidence: 99%
“…Nonetheless, people staying at home or closed places spend higher hours on watching television or using digital media for entertainment purposes (AACAP, 2020;Király et al, 2020;UNICEF, 2020). Previous research shows screen time is associated with a wide range of noncommunicable diseases among the vulnerable individuals (Janssen et al, 2020;Kuss & Griffiths, 2012;Lanca & Saw, 2020;Wang, Li, & Fan, 2019). Recent empirical studies suggest a rapid increase of digital screen time in different populations during the COVID-19 pandemic (Carroll et al, 2020;Górnicka, Drywień, Zielinska, & Hamułka, 2020;Hu, Lin, Chiwanda Kaminga, & Xu, 2020;Keel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review article on the association between digital screen time and myopia, the authors conclude that the hours spent on digital screen time in children and adolescents and odds of myopia "are mixed" [29], and that the impact of screen time on myopia has to be further evaluated using objective screen time measures. Myopia prevalence appears to have increased primarily with increasing education in urban Asia a few decades ago and not just recently alongside with screen time [29]. There is currently no clear knowledge by how many hours per day exactly screen time in children has increased in Asia over the years, but publically available statistics showing that internet use has grown by a factor of 30 on the average in Asia over the last 20 years of the critical reference period [30] suggest that children's screen times are likely to have increased just as dramatically in the last 20 years.…”
Section: Myopia and Early Blindnessmentioning
confidence: 99%
“…Epidemiologic studies have shown that children who spent more screen time statistically consume fewer fruits and vegetables, and more energy snacks, soft drinks, or fast food, and therefore receive a higher percentage of their energy from fats and a higher total energy intake [36]. Results of a recent survey from the USA revealing the link between the severity of obesity and the number of screen time hours per day in children treated for obesity in different hospitals across the country [29].…”
Section: Obesitymentioning
confidence: 99%